Доступ к средствам правовой защиты в случаях злоупотреблений в области прав человека, связанных с предпринимательской деятельностью - Office of the United Nations High Commissioner for Human Rights (United Nations, 2025)
Over the course of six years, and in response to successive mandates from the Human Rights Council, OHCHR’s Accountability and Remedy Project developed guidance on how to enhance the effectiveness of the three categories of remedial mechanisms covered in the Guiding Principles on Business and Human Rights. For each category of mechanism, OHCHR spent two years consulting with those who use, design, and administer the mechanism, among others, to identify good-practice lessons, resulting in a set of reports presented to the Human Rights Council. This publication compiles the guidance and explanatory notes from those reports focusing on judicial mechanisms